2020
DOI: 10.1111/ijcs.12556
|View full text |Cite
|
Sign up to set email alerts
|

Health motive and the purchase of organic food: A meta‐analytic review

Abstract: There are many empirically determined influential factors known to control the organic food purchase behaviour. Of these known factors‐ health, product quality and concern for natural environmental degradation are seen as the major motives behind the organic food purchase. We, therefore, attempted to investigate the most prominent reason(s) for buying organic food, using the meta‐analyses of studies published during the last 25 years as our basis for conviction. Multilevel meta‐analyses was applied to the stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
173
2
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 238 publications
(215 citation statements)
references
References 66 publications
(113 reference statements)
4
173
2
3
Order By: Relevance
“…Yadav and Pathak (2016) showed the considerable influences of health consciousness and environmental concern on attitude towards organic food, and the positive impact of attitude towards organic food on purchase intention. Rana and Paul (2020) even showed that there were significant differences in the degree of positive impact of health consciousness on attitude towards organic food among the studies that confirmed this relationship. Pham et al (2018) studied factors affecting organic food consumption among young consumers in Vietnam and showed that food safety concern, health consciousness and media exposure caused significant effects on attitude towards organic food, while environmental concern and food taste had insignificant impacts.…”
Section: Literature Reviewmentioning
confidence: 89%
“…Yadav and Pathak (2016) showed the considerable influences of health consciousness and environmental concern on attitude towards organic food, and the positive impact of attitude towards organic food on purchase intention. Rana and Paul (2020) even showed that there were significant differences in the degree of positive impact of health consciousness on attitude towards organic food among the studies that confirmed this relationship. Pham et al (2018) studied factors affecting organic food consumption among young consumers in Vietnam and showed that food safety concern, health consciousness and media exposure caused significant effects on attitude towards organic food, while environmental concern and food taste had insignificant impacts.…”
Section: Literature Reviewmentioning
confidence: 89%
“…Also, the findings of Pearson, Henryks, and Moffitt (2007) suggest that, particularly, individual benefits, that is, health and taste, are of major importance for OFP consumers (in Australia). A meta‐analytic review of the literature on this topic can be found on the work of Rana and Paul (2020)…”
Section: Discussionmentioning
confidence: 99%
“… Meta-analytical reviews are focused on statistical assessments of prior empirical research on a specific research topic, whereby the common effects are identified through consistency in the direction of effect, effect size, and statistical power, and the reason for variations are explained. Examples of meta-analytical reviews include antecedents of foreign subsidiary divestment ( Schmid & Morschett, 2020 ), celebrity endorsements ( Knoll & Matthes, 2017 ), health motives and organic food purchases ( Rana & Paul, 2020 ), and host country risks and foreign ownership strategies ( Tang & Buckley, 2020 ). …”
Section: Methodsmentioning
confidence: 99%